(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to obtain empirical evidence of how it affects capital structure, growth opportunities and earnings persistence on earnings response coefficient. The coefficient in the construction and building sub-sector service companies listed in Indonesia Stock Exchange (IDX) 2013-2017 period. Data analysis and hypothesis testing using panel data regression analysis. The results showed that the variable Capital structure has a negative and insignificant effect on earnings response coefficient. Growth opportunity has a significant positive effect on earnings response coefficient. Earnings persistence has a significant positive effect on earnings response coefficient